Penerapan Model Waterfall Untuk Perancangan Sistem Informasi Penyewaan Studio Musik Pandawa Musik Studio - Alviyan Alviyan; Mohammad badrul (Computer Based Information System Journal, 2026)
Pandawa Musik Studio is a company that offers recording music studio rental services. In running a business, the process of processing report recording data is still done manually, and often causes problems ranging from customer data that clashes with schedules, and is often confused for that it is necessary to create an information system to overcome all these problems, in processing rental data. This web-based music studio rental service is a means to manage and rent between the studio and customers online. Rental rental system where customers / customers do not need to come directly to the location of the place to be able to do the rental they want. Customers can simply do their rental activities hammering the website. The methodology of this study uses the waterfall method. This method is carried out with a systematic approach, starting from the stage of system needs and then to the stage of analysis, design, coding, testing / verification, and maintenance. The step by step traversed must be completed one by one (unable to jump to the next stage) and run in order, therefore it is called waterfall (Waterfall). This music studio rental information system is web-based using programming languages PHP, HTML, CSS, Javascript and using MySQL as its database